Attention and emotion shape self-voice prioritization in speech processing. (January 2023) - Pinheiro, Ana P.; Sarzedas, João; Roberto, Magda S.; Kotz, Sonja A.
Abstract: Both self-voice and emotional speech are salient signals that are prioritized in perception. Surprisingly, self-voice perception has been investigated to a lesser extent than the self-face. Therefore, it remains to be clarified whether self-voice prioritization is boosted by emotion, and whether self-relevance and emotion interact differently when attention is focused on who is speaking vs. what is being said. Thirty participants listened to 210 prerecorded words spoken in one's own or an unfamiliar voice and differing in emotional valence in two tasks, manipulating the attention focus on either speaker identity or speech emotion. Event-related potentials (ERP) of the electroencephalogram (EEG) informed on the temporal dynamics of self-relevance, emotion, and attention effects. Words spoken in one's own voice elicited a larger N1 and Late Positive Potential (LPP), but smaller N400. Identity and emotion interactively modulated the P2 (self-positivity bias) and LPP (self-negativity bias). Attention to speaker identity modulated more strongly ERP responses within 600 ms post-word onset (N1, P2, N400), whereas attention to speech emotion altered the late component (LPP). However, attention did not modulate the interaction of self-relevance and emotion. These findings suggest that the self-voice is prioritized for neural processing at early sensory stages, and that both emotion and attention shape self-voice prioritization in speech processing. They also confirm involuntary processing of salient signals (self-relevance and emotion) even in situations in which attention is deliberately directed away from those cues. These findings have important implications for a better understanding of symptoms thought to arise from aberrant self-voice monitoring such as auditory verbal hallucinations.